The Role of Resilience towards Altruism: Be Strong for Yourself before Anyone Else - Hanna Christina Uranus; Naomi Soetikno; Rismiyati E. Koesma (Journal of Educational, Health and Community Psychology, 2022)
Professional psychologists provide services for clients to heal. Thus, it is important for professional psychology graduate students to have altruism, or a trait in which individuals are consistently more generous, helpful, and kind than the average people. To have altruism, students must have resilience, namely the ability to rise in the face of stressful situations with the following dimensions: (a) personal competence; (b) tolerance to adverse effects; (c) acceptance of changes; (d) control; and (e) spiritual beliefs. The purpose of this study was to examine the role of resilience to altruism. The research took data from 104 students, and data processing was done by linear regression. It was found that overall resilience played a role in altruism. If viewed per dimension, the only dimensions significantly impacting altruism were tolerance to adverse effects and control. Further research can explore the relationship between resilience and altruism in other service-providing professionals.Keywords: Altruism, resilience, professional psychology, graduate students